2003
DOI: 10.2460/javma.2003.223.987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a continuous glucose monitoring system for use in dogs, cats, and horses

Abstract: Our data indicate that use of CGMS is valid for dogs, cats, and horses. This system alleviated the need for multiple blood samples and the stress associated with obtaining those samples. Because hospitalization was not required, information obtained from the CGMS provided a more accurate assessment of the animal's glucose concentrations for an extended period, compared with measurement of blood glucose concentrations. Use of the CGMS will promote the diagnostic and research potential of serial glucose monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 27 publications
(41 reference statements)
3
81
2
1
Order By: Relevance
“…Continuous glucose monitoring represents a technological innovation has been marketed in the human medical field for better studying glucose regulation in individuals with diabetes. 67,68 Briefly, this method entails placing a tiny glucose sensor in a subcutaneous location to render a computerized digital recording (Fig. 1).…”
Section: Use Of Continuous Glucose Monitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous glucose monitoring represents a technological innovation has been marketed in the human medical field for better studying glucose regulation in individuals with diabetes. 67,68 Briefly, this method entails placing a tiny glucose sensor in a subcutaneous location to render a computerized digital recording (Fig. 1).…”
Section: Use Of Continuous Glucose Monitorsmentioning
confidence: 99%
“…Using this method, it is possible to unobtrusively record the concentration of glucose in the interstitial compartment (equivalent to the blood glucose concentration) every 5 minutes over the course of up to 7 days (288 data points per 24-hour period). 67,68 A potential advantage of this method for equine practitioners includes the ability to monitor changes in interstitial tissue glucose concentration over time with minimal need for handling. Using this technique, the authors observed that the interstitial glucose concentration of lean, insulin-sensitive adult horses tends to be maintained at the lower end of the reference range with minimal variance (horses being fed ad libitum low NSC grass hay) ( Fig.…”
Section: Use Of Continuous Glucose Monitorsmentioning
confidence: 99%
“…58,59 Briefly, this method entails placement of a tiny glucose sensor in a subcutaneous location and computerized digital recording. Using this method, it is possible to unobtrusively record the concentration of glucose in the interstitial tissue compartment (equivalent to the blood glucose concentration) every 5 min over the course of up to 7 days (288 data points per 24 h period).…”
Section: 35657mentioning
confidence: 99%
“…A good correlation between interstitial fluid and blood glucose concentrations was shown with the first generation of CGMSs in cats and dogs. [1][2][3][4] However, these older systems necessitate attachment of the monitor to the animal and manual downloading of the recorded data to a computer for analysis. The Guardian Real-Time (Medtronic) is a new generation CGMS that enables onscreen date recording over a 72-h period.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This system measures glucose concentrations in the subcutaneous interstitial fluid every 5 mins for up to 72 h via a glucose oxidase-containing sensor. The technique provides a potentially less stressful alternative to blood glucose measurements and generates detailed glucose curves.…”
Section: Introductionmentioning
confidence: 99%